2019
DOI: 10.1038/s41523-019-0111-0
|View full text |Cite
|
Sign up to set email alerts
|

SETER/PR: a robust 18-gene predictor for sensitivity to endocrine therapy for metastatic breast cancer

Abstract: There is a clinical need to predict sensitivity of metastatic hormone receptor-positive and HER2-negative (HR+/HER2−) breast cancer to endocrine therapy, and targeted RNA sequencing (RNAseq) offers diagnostic potential to measure both transcriptional activity and functional mutation. We developed the SET ER/PR index to measure gene expression microarray probe sets that were correlated with hormone receptors ( ESR1 and PGR ) and robust to prea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1,064
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(1,064 citation statements)
references
References 36 publications
0
1,064
0
Order By: Relevance
“…Recently, several clinical trials have demonstrated that the addition of CDK4/6 selective inhibitors to endocrine therapy has improved progression-free survival as well as overall survival in patients with advanced breast cancer [ 83 , 84 , 85 ]. Since CDK is considered a key molecule for several cell cycle transitions, targeting this pathway has been studied in multiple cancer types in the last decade [ 86 , 87 , 88 , 89 , 90 , 91 ]. However, it also remains challenging to accurately identify patients who respond to the targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several clinical trials have demonstrated that the addition of CDK4/6 selective inhibitors to endocrine therapy has improved progression-free survival as well as overall survival in patients with advanced breast cancer [ 83 , 84 , 85 ]. Since CDK is considered a key molecule for several cell cycle transitions, targeting this pathway has been studied in multiple cancer types in the last decade [ 86 , 87 , 88 , 89 , 90 , 91 ]. However, it also remains challenging to accurately identify patients who respond to the targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted RNA-seq is increasingly being used for clinical diagnostics 25 , 35 , 36 . For solutions requiring, say 25 to a few hundred genes, the cost of a sample’s library preparation is at least comparable to the cost of materials for other technologies.…”
Section: Discussionmentioning
confidence: 99%
“…(accession number GSE20194; n = 278) [51], Symmans et al (GSE25066; n = 508) [24], Vera-Ramirez et al (GSE28844; n = 33) [22], Noguchi et al (GSE32646; n = 115) [52], and Massarweh et al (GSE33658; n = 11) [23]. We used metastasis cohorts (Wang et al GSE2034 [18]; n = 286, Bos et al GSE12276 [17]; n = 204, Siegel et al GSE110590 [20]; n = 16, Sinn et al GSE124647 [53]; n = 140), which have the data of metastatic tumors, to investigate the G2M pathway scores in metastatic tumors. The GSE110590 cohort contained 16 samples of the primary tumors as well as 62 samples of the metastatic tumors from patients with matching primary tumors.…”
Section: Data Of Metabric and Other Breast Cancer Cohortsmentioning
confidence: 99%